Влияние добавок ультрадисперсного порошка металла на характеристики горения ВЭМ - Коротких А. Г. Александр Геннадьевич; Архипов В. А. Владимир Афанасьевич; Глотов О. Г. Олег Григорьевич; Сорокин И. В. Иван Викторович (2016, 2016)
Заглавие с экрана